Investigation of the chemical, strength, adhesion and morphological properties of fly ash based geopolymer-modified bitumen - P. Rosyidi, Sri Atmaja; Rahmad, Suzielah; Md. Yusoff, Nur Izzi; Shahrir, Aini Hazwani; Ibrahim, Ahmad Nazrul Hakimi; Ismail, Nor Farah Nadia; Haji Badri, Khairiah (Elsevier Ltd, 2020)
The current study seeks to investigate the chemical, strength, adhesion and morphological properties of fly-ash based geopolymer-modified bitumen (GMB). The geopolymer was prepared by mixing class F fly ash with alkaline solution (sodium silicate and sodium hydroxide), and was then mixed with an 80/100 penetration grade bitumen at different concentrations of 3, 5, 7 and 9% (by weight of bitumen) to produce the GMB. The chemical and strength properties of the binders were determined using the Fourier Transform Infrared Spectroscopy (FTIR) and Impact tests, respectively. The Surface Free Energy (SFE) and Atomic Force Microscope (AFM) tests were conducted to establish the adhesion and morphology of the binders. The modification of base bitumen with geopolymer resulting the improvement in structural chain mobility properties and improved storage stability compared to those of the control sample. The result of FTIR analysis showed that the incorporation of geopolymer into base bitumen did not cause any change in the functional groups, where the peaks of aromatic Cdouble bondC stretching is at around 1600 cm−1 (stretch), 1475 cm−1 (stretch) and 900–600 cm−1 (out-of-plane bend). The peak at around 1390 cm−1 clearly shows the stretch of the C-N amine group. The result of SFE test shows that GMB has better resistance to moisture damage. Finally, the AFM analysis revealed morphological changes in all GMB samples. In general, the addition of 5% geopolymer can be considered as is the optimum concentration for bitumen modification.